Primary cutaneous myeloblastic leukemia. - Bonifazi, E.; Milano, A. (European Journal of Pediatric Dermatology, 2010)
Case report. An 8-month-old girl presented from 1 month a right preauricular, quickly grew nodular lesion, treated until our visit with antibiotics for suspected perichondritis of the tragus. Physical examination showed a 3 cm in size, hard-elastic, painful at palpation, with clear-cut borders plaque (Fig. 1). MRI showed an about 3 cm in size, roundish lesion (Fig. 2). Histological examination showed widespread non epidermotropic infiltration, consisting of cells of blastic type, with prominent nucleoli and a high proliferation index (Mib 1/Ki67 80-90 % of the cancer cells). On immunophenotyping these cells were CD34, CD31, LAT, CD33, locally CD61 and CD43 positive. This immunophenotypic finding was consistent with cutaneous localization of acute myeloblastic leukemia. The diagnosis was confirmed by bone-marrow infiltration with the same cells.